Princess of thorns - Jay, Stacey (2014)
After ten years of exile among fairies who teach her to use her magically-enhanced strength and courage, Sleeping Beauty's daughter Aurora enlists the help of Niklaas, eleventh son of King Eldorio, in the fight to reclaim her throne.
Keywords: Princesses -- Fiction; Princes -- Fiction; Inheritance and succession -- Fiction; Sleeping Beauty (Tale) -- Fiction; Young adult fiction; Adventure fiction; Fantasy fiction